Early childhood mathematics - Sperry Smith, Susan (Boston : Pearson, 2009)
Aligned to the NCTM Standards, this new edition of a trusted text encourages teacher candidates to create an active learning environment that fosters curiosity, confidence, and persistence in children learning mathematics
Foundations, myths, and standards -- Planning for success: a good beginning -- Assessment -- The language of math: communication and representation -- Early math concepts: matching, classification, comparing, and ordering or seriation -- Developing number sense -- Understanding our place value system -- Data analysis: graphing and probability -- Early algebra: pattern and function -- Problem solving: addition and subtraction -- Problem solving: multiplication and division -- Geometry: space and shape -- Measurement -- Thematic units
Includes bibliographical references and index
Keywords: Mathematics -- Study and teaching (Early childhood)